The Effect of “Zep Quiz” in Assessing Students’ Reading Comprehension Skill - Dian Ratnawati; Sri Wahyuni (FKIP - Universitas Riau, 2026)
This study aims to analyze the impact of using Zep Quiz as a game-based assessment medium on students’ reading comprehension skills in English learning. The study is grounded in the need for more engaging and interactive assessment innovations to address students’ boredom and anxiety when facing conventional tests. The research employed a quasi-experimental design with a non-equivalent control group, involving two tenth-grade classes at SMK Kosgoro Nganjuk. The experimental group was assessed using Zep Quiz, while the control group took a traditional paper-based test. Data were collected through a reading comprehension test and a learning motivation questionnaire. The findings indicate that the experimental group’s average score (78.5) was slightly higher than that of the control group (76.1), although the difference was not statistically significant (p = 0.254). Nevertheless, the use of Zep Quiz was proven to enhance students’ motivation, engagement, and comfort during the assessment process. Interactive features such as avatars, real-time feedback, and a competitive atmosphere helped reduce anxiety and foster a stronger learning spirit. These results suggest that Zep Quiz serves as a valid, enjoyable, and academically reliable digital assessment alternative.